Hepatocellular carcinoma: current management and perspectives for the future - Rahbari, Nuh Nabi; Mehrabi, Arianeb; Mollberg, Nathan M.; Müller, Sascha A.; Koch, Moritz; Büchler, Markus W.; Weitz, Jürgen (Annals of surgery, 2011)
Objective: - To review the literature on current management of hepatocellular carcinoma (HCC). - Background: - Hepatocellular carcinoma represents one of the most common malignancies worldwide with a rising incidence in western countries. There have been substantial advances in the surgical and medical treatment of HCC within the past 2 decades. - Methods: - A literature review was performed in the MEDLINE database to identify studies on the management of HCC. On the basis of the available evidence recommendations for practice were graded using the Oxford Centre for Evidence-based Medicine classification. - Results: - Advances in surgical technique and perioperative care have established surgical resection and orthotopic liver transplantation (OLT) as primary curative therapy for HCC in noncirrhotic and cirrhotic patients, respectively. Primary resection and salvage OLT may be indicated in cirrhotics with preserved liver function. Selection criteria for OLT remain debated, as slight expansion of the Milan criteria may not worsen prognosis but is limited by organ shortage and prolonged waiting time with less favorable outcome on intention-to-treat analyses. Strategies of neoadjuvant treatment before OLT require evaluation within prospective trials. Transarterial chemoembolization is the primary therapy in patients with inoperable HCC and compensated liver function. Although systemic chemotherapy is not effective in patients with advanced HCC, there is recent evidence that these patients benefit from new molecular targeted therapies. If these agents are also effective in the neoadjuvant and adjuvant setting is currently being investigated. Furthermore, selective intra-arterial radiation therapy represents a promising new approach for treatment of unresectable HCC. - Conclusions: - Recent developments in the surgical and medical therapy have significantly improved outcome of patients with operable and advanced HCC. A multidisciplinary approach seems essential to further improve patients' prognosis.